Iniciativas socioeconômicas coletivas em Ponta Grossa (PR): alternativas para uma nova economia - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The present thesis was written during a period marked by the consequences of a political crisis that unfolded in recent years in Brazil and the global crisis caused by the COVID-19 pandemic. In this context, the observation of the activities of Varal das Mina, a collective female outdoor sales initiative created in 2018 in Ponta Grossa (PR), served as inspiration for the research project that gave rise to the thesis. The aim of the thesis was to analyze socio-economic initiatives of a collective nature identified in Ponta Grossa that could be considered as alternative development models, with specific objectives of understanding the origins, main characteristics, and needs of these initiatives. The research was conducted in two simultaneously developed stages: exploratory and descriptive research, which aimed to identify, select, and collect data on collective socio-economic initiatives in Ponta Grossa, and bibliographic research, which sought to characterize these initiatives as a specific segment of the lower circuit of the urban economy and reflect on the coexistence of a multitude of economic perspectives and experiences. In addition to Varal das Mina, two other initiatives with different characteristics and origins were analyzed: the Associação de Feirantes da Economia Solidária (AFESol), created in 2012 by a group of artisans with the support of the Incubadora de Empreendimentos Solidários (IESol/UEPG), and the Collective Purchase of the Rede Anunciação de Agroecologia (RAA), a project developed by the Laboratório de Mecanização Agrícola (Lama/UEPG) starting in 2020.
Keywords: Circuitos da economia; Economia Solidária; Economia Feminista; Redes de consumo; Consumo responsável; Circuits of the economy; Solidarity Economy; Feminist Economy; Consumer networks; Responsible consumption; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA